Analyzing The Relationship Between Exchange Rate Volatility and Export Performance In Developing Countries - Lin Wei-Chen; Chen Ming-Hua; Zhang Xian-Li (International Journal of Economics and Management Sciences, 2024)
This study analyzes how exchange rate volatility influences export performance in developing countries. Using data from multiple industries, the research examines how fluctuations in currency values affect trade volume, pricing strategies, and international competitiveness. The findings provide insights into the challenges exporters face and offer policy recommendations to mitigate the adverse effects of currency instability on exports.